Penundukan Militer pada Pengadilan Khusus Tertentu: Non Yustisiabel Peradilan Militer - Tetty Melina Lubis; Arief Fahmi Lubis; Parluhutan Sagala; Tiarsen Buaton (Sekolah Tinggi Ilmu Ekonomi Pariwisata Indonesia Semarang, 2023)
Military courts are regulated through Law No. 31 of 1997 concerning Military Courts. The authority of the military court is authorized to adjudicate criminal acts (general and military, ed), of course, those whose crimes are committed by soldiers of the Indonesia National Army (TNI). The purpose of this study is to show how the military is subordinated in special courts. Qualitative research uses a descriptive approach to collect data systematically, factually, and quickly according to the description when the research is carried out. The results of this study show that it confirms that the military is also subject to the provisions of a special court.